Development of a polarized hyperspectral imaging system for investigation of absorption and scattering properties. Issue 4 (August 2019) - Xu, Jun-Li; Gobrecht, Alexia; Gorretta, Nathalie; Héran, Daphné; Gowen, Aoife A; Bendoula, Ryad
This study was carried out to investigate the feasibility of an original polarized hyperspectral imaging setup in the spectral range of 400–1100 nm for enhancement of absorbance signal measurement on highly scattering samples. Spatial response and spectral calibration have been verified, indicating the consistency of this system and reliability of the acquired data. Model samples consisting of layered sand were prepared and used to uncover the hidden spectral information. In the model matrix, sand worked as scattering particle and dye E141 as absorbing material. Cross (R ⊥ ) and parallel (R | | ) reflectance signals, along with the back-scattered reflectance, R BS (R | | +R ⊥ ) and the weakly scattered reflectanceR SS (R | | −R ⊥ ) spectra were computed and compared. Results demonstrated that cross-polarized images showed more subsurface information from the second layer due to the rejection of the superficial reflectance, while weakly scattered reflectance (R SS ) preserved only the surface information from the first layer. In addition, polarized light spectroscopy absorbance based on Dahm's equation in the frame of the representative layer theory and standard normal variate preprocessingR BS spectra were also obtained from the prepared model matrix. The visual inspection of spectral curves revealed thatR SS / R BS and PoLiS absorbance showed two narrow peaks at 405 nm and 630 nm that were less impacted by multi-scattering effects. Partial least squares regression models were developed to predict dye concentration in the mixture sample. Consistent with the spectral profiles, R SS / R BS and PoLiS absorbance presented the best model performances with determination of coefficients of prediction (r 2 Pred ) equal to 0.96 and 0.95, respectively. The resulting distribution maps of S1/S2 sand sample again confirmed the superior performance ofR SS / R BS and PoLiS absorbance, manifesting their better ability to reveal chemically related information. The overall results obtained in this research showed that the developed polarized-hyperspectral imaging system coupled with scattering correction methods has great potential for the analysis of powdered or turbid samples.